Implications of plasma concentrations of adiponectin in patients with coronary artery disease. Issue 5 (14th April 2004) - Nakamura, Y; Shimada, K; Fukuda, D; Shimada, Y; Ehara, S; Hirose, M; Kataoka, T; Kamimori, K; Shimodozono, S; Kobayashi, Y; Yoshiyama, M; Takeuchi, K; et al.
Abstract : Objective: To investigate whether concentrations of plasma adiponectin constitute a significant coronary risk factor, with particular focus on the relation between plasma concentrations of adiponectin and the development of acute coronary syndrome (ACS). Subjects and methods: Plasma concentrations of adiponectin were measured in 123 patients with coronary artery disease (CAD) and in 17 control participants. Patients were divided into three groups according to condition type: acute myocardial infarction (AMI) group (n  =  59), unstable angina pectoris (UAP) group (n  =  28), and stable angina pectoris (SAP) group (n  =  36). Results: Plasma concentrations of adiponectin correlated negatively with body mass index ( r  =  −0.18, p < 0.05), serum triglyceride ( r  =  −0.25, p < 0.01), and fasting glucose concentrations ( r  =  −0.21, p < 0.05), but correlated positively with age ( r  =  0.26, p < 0.01), high density lipoprotein cholesterol concentrations ( r  =  0.35, p < 0.01), and low density lipoprotein particle size ( r  =  0.37, p < 0.01). Plasma concentrations of adiponectin in patients with ACS, in both the AMI and UAP groups, were significantly lower than those in patients with SAP and in the control group (ACS, 6.5 (3.0) μg/ml; SAP, 11.3 (5.9) μg/ml; control 12.8 (4.3) μg/ml; p < 0.01). Additionally, plasma concentrations of adiponectin in patients with CAD (7.9 (4.6) μg/ml, p < 0.01) were significantly lower than in the control group. There were, however, no significant differences between patients with SAP and the control group (p  =  0.36). Multiple logistic regression analysis showed that smoking, fasting glucose concentration, and low log adiponectin concentration correlated independently with the development of an ACS. Conclusions: The findings suggest that measurement of plasma concentrations of adiponectin may be of use for assessing the risk of CAD and may be related to the development of ACS.